CSC711: Advanced Software Engineering / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2017)
The course aims to develop the depth understanding of the discipline of software engineering by considering the wider systems engineering context in which software plays a role. It aims to examine the principles, concepts and techniques associated with a number of advanced and industrially relevant topics, relating to both the product and processes of software engineering. It seeks to complement this with an account of the associated practical and professional issues in software engineering.